The Effectiveness of Rational Emotive Behavior Therapy Approach Using a Group Setting to Overcome Anxiety of Students Facing Examinations - Misdeni Misdeni; Syahniar Syahniar; Marjohan Marjohan (International Journal of Research in Counseling and Education, 2019)
Purpose of this study was to examine the effectiveness of the approach Rational Emotive Behavior Therapy setting group in overcoming the anxiety of students facing exams at SMP Negeri 1 Lubuk Alung. This type of research is quantitative using an experimental approach.The research subjects were students of class VIII.2, amounting to 10 students, with moderate, high and low levels of anxiety. The instrument used was Anxiety Questionnaire using a model Likert scale. Data analysis using descriptive statistics Wilcoxon Single Rank with 20.00 SPSS test. The results of the study show that in general the group activities using the approach REBT effectively change the anxiety of students facing exams. Specifically: (1) Describe the form of anxiety students face in examinations before treatment (pre-test), (2) Describethe form of students' anxiety in facing the test after treatment (post-test), and (3) Testingthe effectiveness of the approach Rational Emotive Behavior Therapy settings to group to overcome students' anxiety in facing examinations in junior high school.